FAKTOR-FAKTOR YANG MEMENGARUHI KEJADIAN BURNOUT PADA PERAWAT: LITERATUE REVIEW - Nuraini, Syarifah Try; Putri, Triyana Harlia; Anggraini, Rara (Department of Nursing, Faculty of Medicine, Universitas Tanjungpura, 2024)
Background: Nurses are one of the human resources in hospitals whose numbers dominate health workers as a whole and establish long-standing relationships with patients and their families. Nursing jobs have high work demands, such as routine work, tight work schedules, responsibility for the safety and health of themselves and others, and are required to be able to work in teams. The complexity of the demands of work and the existing responsibilities causes nurses to be prone to burnout. Purpose: Describe the level of burnout, characteristics of nurses, factors that influence / cause burnout in nurses.Method: Literature Review research with article sources obtained through the Garuda Portal, Google Scholar, Neliti, PubMed, ProQuest and Researchgate, using the SPIDER model analysis method. Result: Found 8 articles related to factors that influence burnout nurses with a discussion of burnout levels, characteristics of respondents and factors that influence burnout incidence in nurses. Conclusion: The burnout level of nurses was categorized into low/light burnout, moderate burnout and severe burnout. The characteristics of nurses consist of age, gender, education, marital status, years of service, personality type and employment status. There are several factors that influence the incidence of burnout in nurses, namely age, gender, marital status, education, leadership, family support, workload, work stress, employment status, area of care, organization, years of service, appreciation, commitment, type of personality and psychological problems. The variable of factor that most often influence the incidence of burnout in nurses are excessive nurse workload, family support, commitment and appreciation. Keyword: burnout, factor, nurses, workload.